OPERATIONALIZING HIFZ AL-NAFS IN ZAKAT GOVERNANCE: Developing a Maqāṣid-Based Framework for Social and Humanitarian Programs - Vina Fithriana Wibisono; Mufti Fitiyani (Malang Prodi. Ahwal Al-Syakhsiyyah, IAI Al-Qolam, 2026)
Zakat governance plays an important role in ensuring that zakat funds are managed in accordance with Islamic principles while addressing social and humanitarian needs. However, limited studies have examined how ḥifẓ al-nafs can be operationalized as a governance framework in zakat management. This study aims to analyze the operationalization of ḥifẓ al-nafs in the management of zakat, infaq, and sadaqah (ZIS) funds through social and humanitarian programs at LAZIS Jateng Solo and to develop a maqāṣid-based governance framework. This qualitative empirical legal research employed a case study approach using interviews, observation, and document analysis. The data were analyzed through thematic analysis within the framework of maqāṣid sharia. The findings reveal three operational dimensions of ḥifẓ al-nafs: Basic Needs Protection, Emergency Response, and Humanitarian Solidarity. These dimensions demonstrate that zakat governance extends beyond fund distribution by promoting social welfare and protecting human life through preventive, responsive, and transformative governance mechanisms. The study proposes a maqāṣid-based governance framework that reconceptualizes ḥifẓ al-nafs from a normative objective into an operational governance principle for social and humanitarian programs, providing a conceptual reference for strengthening maqāṣid-oriented zakat governance.